Hybrid Renewable Energy System: Sustainable Energy Engineering Solutions For The Future - Judijanto, Loso (Pt. Anagata Sembagi Education, 2025)
This study aims to examine the potential contribution of the Hybrid Renewable Energy System in supporting sustainable energy transitions in the future, especially in the context of reducing carbon emissions and dependence on fossil fuels. This study uses a descriptive-quantitative research type with an engineering simulation approach. The study focuses on modeling and analyzing the contribution of a hybrid renewable energy system (HRES) in reducing carbon emissions and reducing dependence on fossil fuels. . Based on the results of observations and analysis of technical data on solar radiation and daily wind speed, photovoltaic (PV)-based renewable energy systems show significant technical potential in generating electricity consistently throughout the year, especially in tropical areas. Meanwhile, although the potential for wind energy is relatively smaller, especially in areas with low average wind speeds, wind turbines can still provide additional contributions — especially when solar conditions are limited such as at night or in the rainy season. By combining these two energy sources into a hybrid system (HRES), the efficiency of renewable energy utilization can be maximized. The combination of PV and wind turbines allows : 1 ) Direct carbon emission reduction, which is 22.7 tons of CO₂ per year from the PV system alone. 2) Diversification of energy sources, which reduces vulnerability to single dependence on fossil fuels. 3) Increasing the reliability of the electricity system, especially for remote areas and areas not yet covered by the PLN network. Overall, HRES provides a practical, efficient, and sustainable solution to meet the energy needs of small to medium-scale communities. It also opens up opportunities for energy decentralization, promotes a green economy, and strengthens Indonesia's commitment to net zero emissions targets in the future.